2022
DOI: 10.3390/agronomy12051013
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Smart Farm Irrigation Systems in Kherson Province: Feasibility Study

Abstract: The growth of the world population requires an increase in food production. Its solution requires the introduction of advanced technologies, including automated irrigation systems. Commercially available smart irrigation systems are not widespread because of their high cost. A low-cost smart irrigation system based on satellite monitoring is proposed to schedule irrigation. The purpose of this study was to investigate the smart irrigation system during five-year field experiments. Water-use productivity, irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…There are several bottlenecks that need to be considered when implementing automated irrigation systems in rice cultivation: Cost: Implementing an automated irrigation system can be expensive, especially for small-scale rice farmers. The cost of the sensors, communication systems, and other equipment needed to set up the system can be a barrier to adoption [51]. Technical expertise: Setting up and maintaining an automated irrigation system requires technical expertise.…”
Section: Bottleneck For Automated Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several bottlenecks that need to be considered when implementing automated irrigation systems in rice cultivation: Cost: Implementing an automated irrigation system can be expensive, especially for small-scale rice farmers. The cost of the sensors, communication systems, and other equipment needed to set up the system can be a barrier to adoption [51]. Technical expertise: Setting up and maintaining an automated irrigation system requires technical expertise.…”
Section: Bottleneck For Automated Irrigationmentioning
confidence: 99%
“…Future research is needed to optimize the energy efficiency of automated irrigation systems for rice cultivation, including the use of renewable energy sources such as solar power. Economic viability: The economic viability of automated irrigation systems for rice cultivation needs to be further evaluated, including the costs and benefits of different types of sensors, decision support systems, and energy sources [51]. Future research is needed to identify strategies to improve the profitability and marketability of automated irrigation systems for rice cultivation.…”
Section: Bottleneck For Automated Irrigationmentioning
confidence: 99%
“…The results showed that the average water use efficiency increased from 4.09% (wheat) to 9.8% (sunflower). The payback period of wheat production has been reduced to 82 months under the proposed system [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Irrigation systems that utilize sensors and machine learning algorithms have been developed to address these challenges [7]. However, many of these systems are complex, expensive, and require a high level of literacy, limiting their use in rural communities [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%